Cebula, Cybulin, Cybulski, czyli co wspólnego ma nazwisko Cybulski z cebulą - Marciniak-Firadza, Renata (Acta Universitatis Lodziensis. Folia Linguistica, 2017)
The purpose of the article is to track the etymology of the word onion and its meanings in the history of the Polish language, contemporary Polish and local dialects, paying attention to verbal, phraseological connections which it creates, proverbs and sayings, as well as derivatives of both common, as well as proper names. The purpose is also to show connections of the common name of onion and proper name Cybulski. The source material for analysis was excerpted from dictionaries of the Polish language: etymological, phraseological, onomastic, dialectal and general (explanatory). Exceptionally in case of environmental variants of the Polish language, date comes from websites.